Controlling Spodoptera exigua Using Parasitoid Trichogramma japonicum in Acacia Nurseries (Acacia crassicarpa) at Kerinci Central Nursery PT. Riau Andalan Pulp & Paper - Betti Andriany Sirait; Rusli Rustam; Hafiz Fauzana (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2023)
Armyworm (Spodoptera exigua Hubner.) is the main pest of acacia. Controlling such pests generally uses synthetic insecticides, which cause negative impacts such as they would resistance & resurgence, environmental pollution, residual effects, secondary pest explosions, and reduced biodiversity. We need an alternative in pest control, such as using parasitoid Trichogramma japonicum. This study aims to test the parasitism after the release of Trichogramma japonicum on Spodoptera exigua eggs in Acacia crassicarpa nurseries. The research was carried out at the Kerinci Central Nursery PT. RAPP on October 2019-March 2020. The research started with exploring, rearing and releasing parasitoid Trichogramma japonicum. The treatment was plotted with and without releasing Trichogramma japonicum on Spodoptera exigua eggs for seven days of observation and analyzed using T-test at a 5% level. The significance of Trichogramma japonicum parasitized eggs in Spodoptera exigua eggs was 41.9% after releasing parasitoids in Acacia crassicarpa nurseries. The highest parasitization by Trichogramma japonicum was in the 3rd plot with an average parasitization of 53.8% and the lowest was in the 1st plot with an average 31.3% parasitization. Trichogramma japonicum that emerged from the total mass of eggs brought to the laboratory after parasitized eggs were 14.2%. Trichogramma japonicum showed significantly different results in reducing the egg population of Spodoptera exigua in the mother plant nursery Acacia crassicarpa.